Anarchetypes : A Re-evaluation of Marginal Literary Forms and Genres - Braga, Corin, (Textxet: Studies in Comparative Literature ;, 2026)
Why have literary works and corpuses - such as ancient Greek-Roman novels, Renaissance chivalric literature, early modern extraordinary voyages, classical French and English romances, or modern fantasy - been rejected from the canon of high literature? This volume aims at introducing the concept of anarchetype, in contrast to the concept of archetype, in order to define the "flawed design" of texts which, contrary to the Aristotelian tradition, have no closed structure or global organic meaning. This new-formalist approach will allow the re-evaluation of literary narrative and genres which have been judged by rhetors and theorists as marginal leftovers and failures devoid of aesthetic value. Contributors are: Maria Barbu, Carmen Borbély, Corin Braga, Ruxandra Cesereanu, Marius Conkan, Laura T. Ilea, Călina Părău, Radu Toderici, and Alex Văsieș.